2005
DOI: 10.1016/j.antiviral.2005.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Identification of natural compounds with antiviral activities against SARS-associated coronavirus

Abstract: More than 200 Chinese medicinal herb extracts were screened for antiviral activities against Severe Acute Respiratory Syndrome-associated coronavirus (SARS-CoV) using 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium inner salt (MTS) assay for virus-induced cytopathic effect (CPE). Four of these extracts showed moderate to potent antiviral activities against SARS-CoV with 50% effective concentration (EC50) ranging from 2.4 +/- 0.2 to 88.2 +/- 7.7 microg/ml. Out of the fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
465
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 524 publications
(469 citation statements)
references
References 26 publications
2
465
0
2
Order By: Relevance
“…Three extracts (D. heterophyllum, D. tanguticum and S. mussotii) were found to be effective in encephalitis mice induced by HSV-2 infection. Many Chinese traditional medicinal plants showing anti-HSV activity were reported by Li et al (2005) and Cheng et al (2004). However, there is no report of anti-HSV activities for these Tibetan plant extracts in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Three extracts (D. heterophyllum, D. tanguticum and S. mussotii) were found to be effective in encephalitis mice induced by HSV-2 infection. Many Chinese traditional medicinal plants showing anti-HSV activity were reported by Li et al (2005) and Cheng et al (2004). However, there is no report of anti-HSV activities for these Tibetan plant extracts in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The chemical composition of Lycoris type alkaloids havs anti-bacterial activity, some scholars have found that Crinine type alkaloids with broad-spectrum antimicrobial activity [31][32] , Crinine has inhibitory activity against Staphylococcus aureus; Crinine and ainarbellisine have anti-E.coli activity; The hippeastrine of Lycoris type alkaloids has anti-Candida albicans activity [33] ; The chemical composition of Lycoris type alkaloids have anti-viral activity, Lycoris type alkaloids has inhibition effect of flu virus, measles virus, polio virus and SARS virus [34] ; Haemanthidine of Crinine alkaloids have anti-transcriptional activity effect on HIV-1 virus, Homolycorine of Lycoris type alkaloids and Colchicine of Tazettine alkaloids also have anti-transcriptional activity [35] .…”
Section: Anti-bacterial and Anti-viral Effectmentioning
confidence: 99%
“…Lycorine is also effective against Severe Acute Respiratory Syndrome-associated coronavirus (SARS-CoV) 103 . On the other hand, narciclasine inhibits protein synthesis at the step of peptide bond formation.…”
Section: Antimicrobial Activitiesmentioning
confidence: 99%